Pemanfaatan Media Sosial Instagram @humas_jabar Sebagai Sumber Informasi Masyarakat Jawa Barat - Vina Salsabila Firmana; Priyo Subekti (Lembaga Pengembangan Kinerja Dosen, 2024)
Digitalization triggered the development of information and communication technology, giving birth to social media, supported by the internet, as the main gateway for information dissemination. Instagram, as one of the most popular social media platforms, is used by various government agencies to disseminate information effectively. This study aims to determine the utilization of social media in the management of Instagram @humas_jabar, used by the Communication and Informatics Office of West Java Province as a source of information for the people of West Java. This research was conducted using the descriptive qualitative method through observation during job training, interviews with the public relations staff of Diskominfo Prov Jabar, and analysis using the circular model of SoMe. The results of this study indicate that Diskominfo of West Java Province utilizes Instagram @humas_jabar as a public communication tool to disseminate information, innovations, and achievements of its programs. In managing Instagram, @humas_jabar has carried out four stages: share, manage, engage, and optimize.